XÂY DỰNG MÔ HÌNH TỒN KHO TỐI ƯU CƠ BẢN KHI NGUỒN CUNG BỊ GIÁN ĐOẠN - Nguyễn, Hoài Nam (Trường Đại học Đà Lạt, 2023)
Majority of world’s manufactured goods are transported through the intermodal transportation system with containers, making this the most important system for global trade. The intermodal transportation is performed for the cost and time saving. There is a risk of supply disruption in this system. In this paper, basic inventory optimisation model is formed for cost minimisation under supply disruption based on a case study. These models provide a basic understanding about two different strategies which can be used in case of the supply disruption especially disruption of the transportation link.